2019
DOI: 10.2503/hortj.utd-008
|View full text |Cite
|
Sign up to set email alerts
|

The Processing Tomato Cultivar ‘Natsunoshun’ is Susceptible to an Excess or Lack of Soil Moisture after the Flowering Stage

Abstract: An excess or lack of soil moisture are significant abiotic stresses that reduce the average yield for vegetable crops worldwide. The responses of 'Natsunoshun', a processing tomato cultivar, to water stress at three growth stages, first flower differentiation, first flowering, and fruit development, were investigated over a two-year period. The year effect on yield was not significant; however, the growth stage and the type of water stress at a particular growth stage affected yield significantly. Either an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 32 publications
(34 reference statements)
0
0
0
1
Order By: Relevance
“…Prolonged exposure to wet conditions resulted in a greater biomass reduction with a decline in photosynthesis (Fig. 6B), consistent with observations in processing tomatoes (Jitsuyama et al 2019;Ide et al 2022).…”
Section: Water Content and Photosynthetic Parameterssupporting
confidence: 89%
See 1 more Smart Citation
“…Prolonged exposure to wet conditions resulted in a greater biomass reduction with a decline in photosynthesis (Fig. 6B), consistent with observations in processing tomatoes (Jitsuyama et al 2019;Ide et al 2022).…”
Section: Water Content and Photosynthetic Parameterssupporting
confidence: 89%
“…Based on previous studies (Jitsuyama et al 2019;Ide et al 2022), the wet treatment consisted of maintaining 2-3 cm of water on the soil surface. Since the pots had holes in the bottom for drainage, thick vinyl bags were used to prevent drainage during the wet treatments.…”
Section: Plant Materialsmentioning
confidence: 99%
“…In a previous study, we conducted pot experiments with the cultivar 'Natsunoshun', which is the main cultivar grown in Numata, central Hokkaido. We found that waterlogging treatment after the first flowering stage significantly reduced yields (Jitsuyama et al, 2019).…”
Section: Introductionmentioning
confidence: 65%
“…Processing tomato is one of the vegetable crops that will potentially benefit from these water table control systems (Jitsuyama et al, 2019). However, it is not feasible to install these systems in all converted paddy fields, and currently, these systems are installed in less than 10% of the total available area of converted paddy fields (Jitsuyama et al, 2019). Without these systems, heavy rains are likely to produce excess moisture conditions in the clay soils of the converted paddy fields.…”
Section: Introductionmentioning
confidence: 99%
“…Maka dari itu Penyiraman harus dilakukan pagi dan sore hari agar kondisi tanaman dan kesuburan tanah tetap terjaga kualitasnya, namun pemupukan sendiri biasanya diberikan pada saat tomat berusia 1 hari dengan menggunakan pupuk kandang. Pupuk cair biasanya diberikan pada saat tomat berusia 15-20 hari supaya organnya sehat dan tidak di terserang hama [6].…”
Section: Pendahuluanunclassified